Simulium (Inaequalium) margaritatum, a new species of black fly (Diptera: Simuliidae) from the central region of Bahia State, Brazil - Pepinelli, Mateus; Hamada, Neusa; Luz, Sérgio L.b. (Zootaxa, 2006)
A new species of black fly, Simulium (Inaequalium) margaritatum, is described based on the male, female, pupa, and larva. This new species was collected in small streams in the Chapada Diamantina National Park and surrounding area in the state of Bahia, Brazil.